PRIMARY EOSINOPHILIC COLITIS WITH CONCOMITANT NEWLY DIAGNOSED INFLAMMATORY BOWEL DISEASE – A DIAGNOSITIC CONUNDRUM. (26th January 2023) - Miranda, Clive; Ali, Murad; Gregory, Elizabeth; Akbar, Matthew; Soofi, Yousef; Ismail, Mayada
Abstract: Eosinophilic colitis (EC) is a rare primary condition characterized by eosinophilic infiltration of the colon in the absence of secondary causes. Affecting only 0.003% of people in the United States, clinical manifestations of the disease can range from abdominal pain, bloody stools, and diarrhea to colonic obstruction, intussusception, volvulus, and perforation. The diagnosis is made upon histopathological analysis of colonic biopsies with the inflammatory infiltrate consisting predominantly or exclusively of eosinophils with focal collections greater than 100 per high-power field (hpf). Unlike inflammatory bowel disease (IBD), granulomas, crypt architectural distortion, pseudopyloric metaplasia, and fibrosis are not usually present with EC, but differentiating between the two conditions has proven to be difficult over the decades. A 33-year-old male with a history of ulcerative colitis since the age of 23 currently on mesalamine presented to the clinic for follow-up. He was officially diagnosed 10 years ago after being hospitalized with bloody bowel movements. Flexible sigmoidoscopy at the time showed confluent, erythematous, ulcerated mucosa suggestive of moderate to severe colitis seen extending from the rectum to 40cm. Rectosigmoid pathology showed distorted crypt architecture with increased lymphoplasmacytic infiltrate in the lamina propria and markedly increased neutrophils within crypt epithelial cells, indicative of ulcerative colitis. He was started on mesalamine and a prednisone taper but was poorly compliant. He presented again 5 months ago with abdominal pain and bloody diarrhea and was given steroids with follow-up colonoscopy. This time, findings showed scattered inflammation and aphthous ulcers throughout the colon with systemic loss of vascularity. Biopsies were negative for any evidence of active inflammatory bowel disease. Pathology showed mildly distorted crypts and significantly increased lamina propria eosinophils >100/hpf consistent with eosinophilic colitis. Bloodwork, including ESR and CRP, were normal. The patient was continued on mesalamine and as needed steroids with good symptom control. Our case highlights a rare phenomenon of primary eosinophilic colitis with newly diagnosed ulcerative colitis. It is difficult to ascertain which disease at which time contributed to our patient's symptoms as the timeframe of both conditions likely overlap. His mild crypt architectural distortion and absence of lymphoplasmacytic infiltrate upon the repeat colonoscopy is indicative of well-controlled ulcerative colitis. There were no other etiologies ascertained for his colonic eosinophilia. Our case demonstrates the diagnostic obscurity of EC in its ability to masquerade as IBD. We aim to educate gastroenterologists on the timely diagnosis and effective management of this disease in order to prevent serious patient complications.